Maximizing Automated Teller Machines (ATM) User Loyalty through Trust and Quality Service: Memaksimalkan Loyalitas Pengguna Anjungan Tunai Mandiri (ATM) melalui Kepercayaan dan Layanan Berkualitas - Sarmigi, Elex; Hizazi, Achmad; Rahayu, Sri; Arum , Enggar Diah Puspa (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2023)
The purpose of this research is to look into the direct and indirect effects of service quality and trust on customer loyalty, as mediated through customer satisfaction. The study is based on a sample of 85 customers who used ATM services at the PT. Bank 9 Jambi, Kerinci Branch. This Study approach is used to calculate sample size, and data is collected utilizing an incidental sampling strategy using a questionnaire. For data analysis, Smart PLS 3.0 software is used to assist path analysis. According to the findings, neither service quality nor trust have a statistically significant influence on customer loyalty, whether directly or indirectly through customer pleasure. Customer pleasure, on the other hand, has a positive and considerable impact on customer loyalty. Furthermore, the study discovers a favorable and significant link between service quality and client trust. These findings provide light on the complex dynamics of service quality, trust, customer satisfaction, and loyalty in the context of ATM usage, providing valuable insights for customer relationship management practitioners and researchers.